Hubungan Bentuk Alas Kaki Terhadap Terjadinya Iliotibial Band Syndrome Pada Komunitas Pelari - Sari, Mediano Melania Kartika; Sudaryanto, Wahyu Tri (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2024)
Running is a form of physical activity that is popular internationally because of its low cost and easy accessibility. Running communities and events are increasingly mushrooming, making the sport of running increasingly lively and popular with all groups. Iliotibial Band Syndrome is the second most common injury in runners after patellofemoral pain syndrome. Shoe components are considered important for providing cushioning and shock absorption when running so that runners avoid iliotibial band syndrome injuries. Objective: To determine the relationship between footwear shape and Iliotibial Band Syndrome in the runner community. Method: This research is quantitative by obtaining data using a survey method. This research used a cross sectional study. Results: Based on bivariate tests, the results were obtained. Conclusion: In this study, it was concluded that there was a relationship between the shape of footwear and the incidence of iliotibial band syndrome in runners.